Critical-Path Dead-End Detection versus NoGoods: Offline Equivalence and Online Learning - Steinmetz, Marcel; Hoffmann, Jörg (Proceedings of the International Conference on Automated Planning and Scheduling, 2017)
One traditional use of critical-path heuristic functions is as effective sufficient criteria for unsolvability. To employ this for dead-end detection, the heuristic function must be evaluated on every new state to be tested, incurring a substantial runtime overhead. We show herein that the exact same dead-end detector can be captured through a nogood, a formula phiOFF computed once prior to search. This is mostly of theoretical interest, as phiOFF is large. We obtain practical variants by instead incrementally generating a stronger nogood psi, that implies phiOFF, online during search, generalizing from already tested states to avoid future heuristic-function evaluations.